Manager@Work: Growing the university of the future - Abd Razak, Dzulkifli (2008)
The title of Universiti Sains Malaysia's submission which runs into more than 100 pages to the Ministry of Higher Education for consideration as an Apex (Accelerated Programme for Excellence) university is "Transforming Higher Education for a Sustainable Tomorrow". Indeed, its vicechancellor, Tan Sri Dzulkifli Abdul Razak, strongly believes that there is a need to transform higher education if Malaysian universities are to be sustainable, and to remain relevant to society. In the following excerpt from his interview with Dorothy Teoh and Aznita Ahmad Pharmy, he elaborates on the concept of sustainability and the challenge for USM in fulfilling the Apex mandate.